CORE OF STRUCTURAL AND GRAMMATICAL FEATURES OF IDIOMATIC EXPRESSIONS - Abulkhayirov , D.F; Achilbayev , Diyorjon Jamshid ugli (Innovative Development in Educational Activities, 2023)
Phraseology-phraseological units with the same structure and function of comparative research in the study of general and specific features of the studied languages (verbal, adjectival, comparative, phraseological units with sentence content, phraseological units of different structural models), phraseological units whose components are the same (somatisms, onomastic), (components, verbs of action, color components, etc.), having the same type of symbolic meaning (fields and groups of phraseological units with the same semantics) and work is carried out on all phraseological funds of languages. The results of the study show that the study of the entire phraseological system, which is characterized by complexity and inconsistency, can be successful only through an in-depth analysis of individual microsystems that have a common feature and have their own characteristic of the system as a whole. Possible taking this into account, we have chosen for analysis numerous (and typical for any language) subsystems of phraseological units semantically oriented to the person in English and Uzbek.